Differentiation of Patients With Unipolar Depression (UD) and Bipolar Disorder (BD) Based on the OPCRIT Test - Grudniewski, Kacper; Pieprz, Natalia; Dąbrowska, Katarzyna; Radecka, Paulina; Wesołowski, Jakub; Zwiech, Dominika; Pawlak, Joanna; Miechowicz, Izabela (Przegląd Psychologiczny, 2025)
Objective: The frequency of bipolar disorder (BD) is estimated at 2% in the global population, while unipolar disorder (UD) is estimated at 3.8%. Despite the prevalence of these disorders, the conversion rate from UD to BD is approximately 6.5%. The aim of the study was to use the OPCRIT (The Operational Criteria Diagnostic Checklist) questionnaire to identify additional elements beyond the diagnostic criteria that would allow for better differentiation between the two groups of patients. Method: The responses of 587 people with BD and 250 people with UD were analyzed. The Mann-Whitney test, the χ² (chi-squared) test of independence, and the Fisher-Freeman-Halton exact test with Bonferroni correction were used for data analysis. A ROC analysis was also performed, the area under the ROC curve (AUC) was calculated, and the optimal cut-off point was determined along with sensitivity and specificity. The calculations were performed using PQStat (v. 1.8.6, PQStat Software) and Statistica (v. 13.3, TIBCO) software. Results: Upon analyzing individual sections of the OPCRIT questionnaire, we identified those of its components that can be used to accurately diagnose BD. We also formulated questions that initially seemed less diagnostically relevant, but statistical analysis revealed significant differences in the responses of both patient groups. Conclusions: The use of the OPCRIT questionnaire in the diagnostic process allows for precise differentiation between patients with BD and UD. The use of OPCRIT can directly contribute to an increase in the frequency of accurate BD diagnoses.